PERENCANAAN EKO-DRAINASE SUMUR RESAPAN SEBAGAI UPAYA PENCEGAHAN BANJIR DI KECAMATAN BINANGUN KABUPATEN BLITAR - Fanani, Zainal; Risma Dwi Atmajayani; Nindya Yusniartanti (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
The existence of land use change and loss of water catchment areas causes environmental ecosystems to be disrupted. Previously, green land has changed its function to become a development area which causes an increase in the volume of surface water when it rains because the water is not reabsorbed by the soil. In October 2022, there was a flood in the Binangun sub-district which was caused by the overflow of the drainage canals and rivers due to the large volume of surface water that entered. As an effort to deal with the flooding problem that occurs, planning infiltration wells is an effective solution to reduce the volume of surface water in the Binangun sub-district. Infiltration well planning was carried out with hydrological analysis and design discharge with a rational calculation method. From the analysis, it was found that the planned debit value was 284.61m3/s. The soil permeability value was obtained from the Falling Head soil sample test. The permeability test results of the falling head method obtained soil permeability values ​​in 3 regions namely, North = 0.003094m/s, Middle = 0.002827m/s, South = 0.001525m/s. The planning results showed that the dimensions of the infiltration wells for the Southern region are R=0.5m, L=1.5m, and H=6m with the assumption that the number of design wells is 333 which can reduce the planned discharge in the Binangun sub-district area by 35%. Keywords: Infiltration Wells; Floods; Drainage Planning.